Research Anthology on Preparing School Administrators to Lead Quality Education Programs (3 Volumes) - Information Resources Management Association (Information Science Reference, 2020)
This book offers theoretical and pedagogical research concerning the management of educational systems on both the national and international scale. It also explores academic administration as well as administrative effectiveness in achieving organizational goals